Acciones dirigidas a la supervivencia de las pymes dedicadas al sector hotelero en Colombia (2017)
The hotel industry of Colombia has had a remarkable growth in the last 25 years (1990 and following), thanks to several factors, among which stand out the support that the state has given to it, in the credit areas and in the impulse to the investment in this area, to foreign and national investors, who see great possibilities in the country for their investment bets to succeed. This, thanks to the good development that the economy has experienced and that has allowed the country to show itself as a stable nation, as far as the economy is concerned.